Barbarische Bürger : Die Isaurier und das Römische Reich - Feld, Karl (2012)
The Isaurians, a mountain people from Asia Minor, challenged Roman rule for over 600 years. Though one Isaurian did make it onto the Eastern imperial throne,they were never successfully integrated. Karl Feld'sstudy brings together, and critically assesses, all the available documentation on the Isaurians and presents it systematically in chronological order.